2017
DOI: 10.7759/cureus.1726
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Echocardiographic Follow-up after Successful Percutaneous Transvenous Mitral Commissurotomy

Abstract: BackgroundThe objective of the study was to determine the long-term outcomes, including mitral restenosis and regurgitation, after successful percutaneous transvenous mitral commissurotomy (PTMC).MethodsThis cross-sectional prospective study was conducted at the cardiology department of Lady Reading Hospital, Peshawar, Pakistan, from January 2007 to December 2009. A total of 84 patients were followed up for a period of 96 months. Pre and post percutaneous transvenous mitral commissurotomy echocardiography was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…[17][18][19] In term of left ventricular function, there is a notion that MS protects the LV, thus systolic function should be preserved [13]. Many studies have shown that the EF is indeed preserved pre and immediately post PTMC [2][3][4]. Our study further con rms this fact and additionally demonstrates this phenomenon even at 6 months.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…[17][18][19] In term of left ventricular function, there is a notion that MS protects the LV, thus systolic function should be preserved [13]. Many studies have shown that the EF is indeed preserved pre and immediately post PTMC [2][3][4]. Our study further con rms this fact and additionally demonstrates this phenomenon even at 6 months.…”
Section: Discussionsupporting
confidence: 78%
“…The aim of PTMC is to relief the obstruction across the mitral valve by cracking open the fused commissures, hence the name "commissurotomy" [1]. There are many studies showing signi cant increases in MVA and reduction in mean PG post PTMC [1][2][3]. PTMC is generally associated with good outcomes with low procedural and long-term mortality, but with signi cant need for re-intervention in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is obvious from the literature that in developing countries like India, MS predominantly affects a younger population and the majority of symptomatic MS patients usually present before the age of 30 years and our findings are in agreement with these studies. [151617181920212223] On the other hand, in Western countries, the disease primarily involves the older population as shown in a series of PTMC reported from developed countries. [24] In addition, reports indicate that the progression of symptoms of rheumatic MS in this part of the world is very rapid.…”
Section: Discussionmentioning
confidence: 99%